Microwave Promoted Synthesis of 2,5-Diaryl-1,3,4-oxadiazoles Using Melamine Formaldehyde Resin Supported Sulfuric Acid - Lei*, Yingjie; Liu, Shuying; Li, Hao; Ding, Mei (Asian Journal of Chemistry, 2013)
A simple and convenient procedure for the synthesis of some 2,5-diaryl-1,3,4-oxadiazoles by reaction of carboxylic acids with (un)substituted benzoic acid hydrazides using melamine formaldehyde resin supported sulfuric acid as dehydration reagent under microwave-accelerated solvent-free condition has been developed. Structures of the corresponding products were elucidated by IR and 1H NMR spectra and elemental analysis. Results showed that most of the synthesized compounds displayed large Stokes shifts of fluorescence emission.